Quantifying Employment Barriers for People with Disabilities: A Statistical Investigation into Inclusivity Challenges - Cruz, Jessica M. Dela; Encinares, Glaize Yvette A.; Garces, Faye Anne D.; Ramirez, Crisanto S. (The Indonesian Institute of Science and Technology Research, 2024)
This study aimed to investigate the types and frequency of employment barriers experienced by individuals with disabilities in Daet, Camarines Norte. Data were collected using a survey questionnaire employing a 4-point Likert scale, employing a descriptive and mixed-method approach. Statistical analysis included percentage technique, weighted mean, and multiple response analysis. The study involved fifty (50) employed and unemployed individuals with disabilities, selected through purposive and quota sampling. Findings indicated several prevalent employment barriers, including insufficient technological support, social exclusion due to physical impairments, inadequate facility modifications for accessibility, relegation to menial tasks, lack of employer awareness regarding disability employment laws, and managerial awareness of equal opportunity concepts without corresponding motivation for action.